2010
DOI: 10.1111/j.1095-8649.2010.02670.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic signatures in an invasive parasite of Anguilla anguilla correlate with differential stock management

Abstract: In this article, it is shown that available genetic tools for the omnipresent parasite Anguillicoloides crassus in European eels Anguilla anguilla are sensitive to different immigration rates into local A. anguilla stocks for two separated river systems. Relying on four highly polymorphic microsatellite markers, it was inferred that under natural recruitment, nematode samples meet Hardy-Weinberg expectations for a single panmictic population, while genetic signals show signs for a strong Wahlund effect most li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Hence, the population genetics of A. crassus has revealed its introduction history. Infrapopulation differentiation in A. crassus was studied in two European rivers, one of which was regularly artificially restocked with eels from a variety of sources and one in which eels had arrived by natural dispersal [ 151 ]. This showed that in the restocked river, A. crassus had high genetic diversity among hosts and a substantial deviation from Hardy-Weinberg equilibrium (see Table 1 ), while in the river with natural recruitment, there was no among-host structuring or deviation from Hardy-Weinberg equilibrium.…”
Section: Influence Of Anthropogenic Disruption On Parasitic Nematode mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the population genetics of A. crassus has revealed its introduction history. Infrapopulation differentiation in A. crassus was studied in two European rivers, one of which was regularly artificially restocked with eels from a variety of sources and one in which eels had arrived by natural dispersal [ 151 ]. This showed that in the restocked river, A. crassus had high genetic diversity among hosts and a substantial deviation from Hardy-Weinberg equilibrium (see Table 1 ), while in the river with natural recruitment, there was no among-host structuring or deviation from Hardy-Weinberg equilibrium.…”
Section: Influence Of Anthropogenic Disruption On Parasitic Nematode mentioning
confidence: 99%
“…This showed that in the restocked river, A. crassus had high genetic diversity among hosts and a substantial deviation from Hardy-Weinberg equilibrium (see Table 1 ), while in the river with natural recruitment, there was no among-host structuring or deviation from Hardy-Weinberg equilibrium. These contrasting patterns were thought to be because the introduced eels had retained A. crassus infrapopulations reflective of their genetically distinct source populations, while A. crassus in the river with natural recruitment are derived from a single population that was already at Hardy-Weinberg equilibrium [ 151 ].…”
Section: Influence Of Anthropogenic Disruption On Parasitic Nematode mentioning
confidence: 99%
“…Populations from Taiwanese aquacultures might not be in Hardy–Weinberg Equillibrium, as this might only fail to be rejected in most markers due to the low sample sizes. It cannot be excluded that Taiwanese isolates are from populations experiencing a strong Wahlund effect, as observed in isolates from the River Rhine ( Wielgoss et al, 2010 ). A continued mixing of population could have resulted in the affiliation of our two different Taiwanese isolates over the European isolates.…”
Section: Discussionmentioning
confidence: 99%
“…It cannot be excluded that Taiwanese isolates are from populations experiencing a strong Wahlund effect, as observed in isolates from the River Rhine (Wielgoss et al, 2010 . As expected, genes with overall higher gene expression had a lower dn/ds, probably because genes with higher expression are under stronger purifying selection (Drummond et al, 2005).…”
Section: Differential Gene Expression Between Sexes Is Negatively Cormentioning
confidence: 99%